The Quasi-Biweekly Oscillation of Winter Precipitation Associated with ENSO over Southern China - Qiaoyu Tong; Suxiang Yao (Atmosphere, 2018)
Using ERA-interim Reanalysis data and observational data, the intraseasonal oscillation of the winter rainfall in southern China is studied. The mean square deviation of daily precipitation is used to express precipitation variability, and winter precipitation variability over southern China is determined to be highly correlated with sea surface temperature (SST) in central and eastern tropical Pacific; the dominant period of the precipitation is 10–30 days, which reflects quasi-biweekly oscillation. Examination of 1000 hPa geopotential height suggests that key low-pressure systems affecting the intraseasonal precipitation come from Lake Baikal, but with different travel paths. In El Niño years, key low-pressure systems converge with other low-pressure systems and move southeastward until reaching South China, while in La Niña years, only one low-pressure system can reach southern China. Meanwhile, the explosive development of the low-pressure system is mainly caused by the joint effects of thermal advection and vorticity advection in El Niño, and only vorticity advection accounted for the dominant status in La Niña. Multiscale analysis shows that the meridional distribution of intraseasonal circulation plays an important role on the thermal transmission and brings strong warm advection from low latitudes to high latitudes in El Niño.